Socio-Economic History of the Mentawai Islands in West Sumatra Province - Bagindo, Muhammad Nur; Chaniago, Maizufri Ilyas; Herwandi, Herwandi; Saga, Syafrizal Sirin; Hussin, Hanafi (Environment-Behaviour Proceedings Journal, 2023)
This study describes the socio-economic history of the population in the Mentawai Islands Regency, West Sumatra, Indonesia. Residents of the area engage in different socio-economic activities. The purpose of this study is to explain the socio-economic life of the majority in agriculture. The research methods used are historical methods, for example, heuristics, criticism, interpretation, and historiography. Mentawai Island residents have been active in the world of agriculture and plantations since the 16th century. At the time when Dutch traders arrived there, the Mentawai Islands were already in contact with ethnic groups who came from the west coast of Sumatra and the surrounding islands.